Pengaruh Fasilitas Kerja Dan Masa Kerja Terhadap Kinerja Aparatur Sipil Negara Di Kecamatan Cipari Kabupaten Cilacap (International Forum of Researchers and Lecturers, 2025)
Government bureaucracy must be managed based on the principles of good and professional governance. Bureaucracy must fully serve the interests of the people and work to provide excellent, transparent, accountable services, and be free from Corruption, Collusion, and Nepotism (KKN) practices. This spirit is the basis for the implementation of government bureaucratic reform in Indonesia. Sub-districts as organizations that provide direct services also need to be supported by complete work facilities because these work facilities are supporting factors for the smooth running of tasks carried out, so that work can be done as expected. Changes in regional government laws clearly affect government organizations including Sub-districts The research method used in this study is a descriptive survey method. The research design uses a quantitative method. The aspects studied in this study include variables (X1) namely work facilities, variables (X2) length of service with variables (Y) namely performance. Data collection tools use observation and questionnaires. The conclusion is: 1. Work facilities tend to be high and ASN performance is very high, so that work facilities have a high influence on ASN performance, meaning that if work facilities are high then ASN performance is very high, while the low indicator in the work facility variable is that the work process should be carried out effectively; 2. Work period tends to be high and ASN performance is very high, so that work period has a high influence on ASN performance, meaning that if work period is high then ASN performance is very high, while the low indicator in the work period variable is that interns with a work period of 0-12 months need to improve the quality of their work; and 3. Work facilities and work period tend to be high and ASN performance is very high, so that work facilities and work period have a high influence on ASN performance, meaning that if work facilities and work period are high then ASN performance is very high thus the proposed hypothesis can be accepted. Meanwhile, the low indicator in the ASN performance variable is that innovation should be carried out in various work programs.